Global integration and world migration - Oded Stark (University of Tübingen, Faculty of Economics and Social Sciences, 2017)
This paper explores the following chain of conjectures: rising use of the internet, the widespread access to global information, and intensified communication between regions and countries brought about, for example, by intensified trade links bring about expansion of people's social space and their set of comparators; this expansion increases people's stress and strengthens their inclination to resort to migration as a means of reducing this heightened stress. Other things held constant, the expansion of people's social space intensifies their inclination to move across geographical space.
urn:nbn:de:bsz:21-dspace-741256
Keywords: A12; A14; B41; D01; F15; F22; J61; O15; Z13; 330; Expansion of social space; Relative deprivation; Migration